Strategi Komunikasi Penerapan Protokol Kesehatan Covid-19 di Masjid Agung Asy-Syuhada’ Pamekasan - Hafidlatul Fauzuna (Jurusan Ilmu Komunikasi UTM, 2022)
This study aims to describe the communication strategy of the management of the Great Mosque of Asy-Syuhada' Pamekasan in implementing the Covid-19 health protocol and to describe maintaining distance when praying together in Islam during a pandemic. This research uses descriptive qualitative method. The result shows that the communication strategy used by the management of the Great Mosque of Asy-Syuhada' Pamekasan is in accordance with the components in the communication formulation in the Laswell concept, Who Says What in Which Channel to Whom With What Effect, which included communicator, message, media, communicant, and effect. The implementation of the health protocol is conveyed to the community or congregation by the mosque management in oral, written and electronic form and had an effect in which the congregation finally complied with the health protocol. Meanwhile, the legal case for keeping a distance in prayer is based on the letter Al-Baqarah verse 195, the hadith of the Prophet Muhammad SAW, and the rule of ushul fiqh. In this case, the case of keeping a distance in congregational prayers during the Covid-19 pandemic is allowed as an effort to prevent the transmission and spread of the virus.